Knowledge, attitude and practices towards e-learning: A feasibility study among first MBBS students of Government Medical College from hilly region of India - Rana, Susheela; Taywade, Onjal K; Medhi, Bandita; Hiwarkar, Monali (Asian Journal of Medical Sciences, 2021)
Background: Nationwide lockdown tremendously affected academic and educational activities of medical students during the COVID-19 pandemic. The medical students like all other faculties resorted to the e-learning modalities. This has helped the first MBBS students to continue learning during this period of lockdown. Hence studies about perception of medical students towards e-learning are relevant. Aims and Objectives: To assess the first MBBS student’s perception about e-learning and online classes. To evaluate feasibility of utilizing e-learning by assessing the acceptability, knowledge, attitude, skills and habits of first MBBS students. Materials and Methods: A questionnaire of 25 questions on various aspects of e-learning was administered to the first MBBS students at Government Medical College, Himachal Pradesh through google form (n=100). They were asked to mark appropriate responses and the data was analysed to get the percentage and proportion on various aspects of e-learning. Results: The first MBBS students widely used e-learning resources to learn anatomy, physiology as well as biochemistry during COVID 19 pandemic. E-learning has made a positive impact on overall learning of first-year subjects, especially anatomy. The responses did not have any association with gender (p>0.05). Conclusion: Distance learning can compensate for conventional teaching during pandemic, but cannot fully replace the traditional teaching in the medical institutes.